Cervical Spine Movement in a Cadaveric Model of Severe Spinal Instability: A Study Comparing Tracheal Intubation with 4 Different Laryngoscopes. Issue 1 (January 2020) - Romito, Jia W.; Riccio, Christina A.; Bagley, Carlos A.; Minhajuddin, Abu; Barden, Catherine B.; Michael, Meghan M.; Bhoja, Ravi; Mootz, Brady L.; Skrivanek, Gary D.; Klein, Kevin W.; McDonagh, David L.
Abstract : Background: This study compared the Macintosh blade direct laryngoscope, Glidescope, C-Mac d-Blade, and McGrath MAC X-blade video laryngoscopes in 2 cadaveric models with severe cervical spinal instability. We hypothesized that the Glidescope video laryngoscope would allow for intubation with the least amount of cervical spine movement. Our secondary endpoints were glottic visualization and intubation success. Methods: In total, 2 fresh cadavers underwent maximal surgical destabilization from the craniocervical junction to the cervicothoracic junction by a neurosurgical spine specialist, with subsequent neutral positioning of the heads with surgical head fixation devices. On each cadaver, 8 experienced anesthesiologists performed four intubations with the 4 laryngoscopes in random order. Lateral radiographic measurements determined vertebral displacement during intubation. Results: Cervical spine displacements were not significantly different amongst video laryngoscopes. Cormack-Lehane Grade 1 views were achieved with all attempts with each of the 3 video laryngoscopes; intubation attempts with the Macintosh blade achieved only grade 3 or grade 4 views. Intubation was successful every time with a video laryngoscope but only during 1 of 16 intubation attempts with the Macintosh blade. Conclusions: In a cadaveric model with maximally destabilized cervical spines, cervical spine movement was observed during attempted laryngoscopy using each of 3 video laryngoscopes, although there was no significant difference between the laryngoscopes. Given cervical spine displacement occurred, these video laryngoscopes do not prevent cervical spine motion during laryngoscopy. However, with improved glottic visualization and intubation success, video laryngoscopes are superior to the Macintosh blade in both cervical spine safety and intubation efficacy in the model studied.